2020
DOI: 10.1108/bfj-09-2020-0771
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fast-food restaurant service quality and its dimensions on customer perceived value, satisfaction and behavioural intentions

Abstract: PurposeThe purpose of this study is to investigate the effect of fast-food restaurant service quality (compound effect of food quality, physical environment quality and employee service quality) and its dimensions (when acting independently) on customer perceived value, satisfaction and behavioural intentions.Design/methodology/approachData was collected from 400 fast-food restaurant customers in Fiji using a public-intercept survey. The study used descriptive and inferential analysis. This research also used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
107
1
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(137 citation statements)
references
References 73 publications
14
107
1
15
Order By: Relevance
“…The store environment is a combination of tangible aspects (fixtures, decorations, colours, lighting, buildings, layout and design) and intangible aspects (music, scent and temperature) (Migdadi & Abdel-Rahman, 2020). Ryu et al (2012) concluded that customers' perceptions of quality (product, service and physical environment) at stores can predict how they perceive value and the degree of satisfaction and thus, their behaviour intention.Customers may interpret whether a product purchase is good quality based on the actual product quality, physical environment, and service encounter (Slack et al, 2020).Also, previous studies in the service sectors have used the combination of interaction quality, physical environment and outcome quality to measure total quality (Namkung & Jang, 2008;Ryu & Han, 2010;Ryu et al, 2012). Therefore, this study aimed to test the components of perceived quality: souvenir quality, service encounter quality and physical quality.…”
Section: Perceived Quality Of Authentic Souvenir Productmentioning
confidence: 99%
“…The store environment is a combination of tangible aspects (fixtures, decorations, colours, lighting, buildings, layout and design) and intangible aspects (music, scent and temperature) (Migdadi & Abdel-Rahman, 2020). Ryu et al (2012) concluded that customers' perceptions of quality (product, service and physical environment) at stores can predict how they perceive value and the degree of satisfaction and thus, their behaviour intention.Customers may interpret whether a product purchase is good quality based on the actual product quality, physical environment, and service encounter (Slack et al, 2020).Also, previous studies in the service sectors have used the combination of interaction quality, physical environment and outcome quality to measure total quality (Namkung & Jang, 2008;Ryu & Han, 2010;Ryu et al, 2012). Therefore, this study aimed to test the components of perceived quality: souvenir quality, service encounter quality and physical quality.…”
Section: Perceived Quality Of Authentic Souvenir Productmentioning
confidence: 99%
“…Service quality can be analysed as a process relating to customers' experiences and needs of the given service (Ferraris et al, 2020). According to Neale et al (2020), service quality has three dimensions: physical consistency, including products such as structures and equipment used; administrative quality, including the organisational identification and attributes; and relational quality, resulting from the relationship between service workers and customers. Service quality has been described as a key factor contributing to higher customer satisfaction, visit intention and improved productivity in the sense of hospitality.…”
Section: Service Qualitymentioning
confidence: 99%
“…Nevertheless, currently, many of these same companies have acknowledged the need to be innovative in their service quality and value offered to distinguish themselves from competitors and, as a result, deliver customer perceived value of the goods they sell (Ferraris et al, 2020). On the other hand, numerous studies (Neale et al, 2020;Liu et al, 2020;Zhang et al, 2020) have shown that service quality positively impacts customer satisfaction, confidence, loyalty, and perceived value. In addition, finding from the previous study by Garg and Kumar (2017) shown that the service quality is the significant factors in student satisfaction towards university food services especially on staff responsiveness.…”
Section: Service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the hierarchical scale developed by Wu and Mohi (2015) was the first model to be specifically developed for fast-food restaurants, but its complex structure composed of 46 items hampers its practical and continuous application to restaurant management systems. Other recent proposals (Oh et al , 2019; Slack et al , 2020) have employed three-dimensional structures to assess service quality in the context of QSR. These studies included the quality of the food, physical environment and employee service rather than the interaction quality dimension suggested by Wu and Mohi (2015).…”
Section: Introductionmentioning
confidence: 99%